2007
DOI: 10.1140/epja/i2006-10383-2
|View full text |Cite
|
Sign up to set email alerts
|

Double pion photoproduction off 40Ca

Abstract: Abstract. The photoproduction of π 0 π 0 and π 0 π ± pairs off 40 Ca has been investigated with the TAPS detector using the Glasgow photon tagging spectrometer at the Mainz MAMI accelerator. Data have been taken for incident photon energies in the energy range from 200 -820 MeV. Total cross sections have been extracted from threshold up to the maximum photon energy and invariant mass distributions of the pion pairs have been obtained for incident photon energies between 400 -500 MeV and 500 -550 MeV. The doubl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 61 publications
3
38
0
Order By: Relevance
“…These calculations, which did not use any effects connected with ππ correlations, could reproduce the observed effect for the π 0 π 0 channel, but they also predicted a similar effect in the semi-charged channel where it had not been seen experimentally. However, a more recent analysis with higher statistics by Bloch et al [10] yielded a result for both charge channels that is in perfect agreement with our calculations (see Fig. 3; the dashed lines in this figure are normalized in height to the data, this normalization reflects uncertainties in the elementary cross sections).…”
Section: Analysis Of Cbelsa/taps ω Photoproduction Datasupporting
confidence: 91%
“…These calculations, which did not use any effects connected with ππ correlations, could reproduce the observed effect for the π 0 π 0 channel, but they also predicted a similar effect in the semi-charged channel where it had not been seen experimentally. However, a more recent analysis with higher statistics by Bloch et al [10] yielded a result for both charge channels that is in perfect agreement with our calculations (see Fig. 3; the dashed lines in this figure are normalized in height to the data, this normalization reflects uncertainties in the elementary cross sections).…”
Section: Analysis Of Cbelsa/taps ω Photoproduction Datasupporting
confidence: 91%
“…Using this in combination with our MAID based vector form factors one obtains the dash-dotted line in Fig. 1 labeled with (2). Even reducing the axial mass to M A = 0.95 GeV it is not possible to get a good description of the ANL data (cf.…”
Section: Excitation Of Spin 3/2 Resonancesmentioning
confidence: 99%
“…Studying semi-inclusive processes in the intermediate energy regime with an energy transfer of 0.1 − 2 GeV, one gains further sensitivity on in-medium changes of baryonic resonances and the nucleon since such modifications may also lead to unexpected final state interaction patterns. A related topic of present interest is the modification of mesons such as, e.g., σ [2] and ω [3] within the medium due to chiral symmetry restoration and/or collisional broadening. A correct understanding of final state interactions is necessary to distinguish profane (e.g., pion rescattering in the nucleus) from spectacular (e.g., chiral symmetry restoration) effects.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference of this setup compared to the previous measurements with TAPS at MAMI [4,5] is the almost 4π coverage of the solid angle and the use of the PID for the identification of charged pions. The primary electron beam of 883 MeV produced bremsstrahlung in a copper radiator of 10µm thickness.…”
Section: Experimental Setup and Data Analysismentioning
confidence: 99%
“…More recently, a shift of the neutral channel spectra increasing with atomic mass number have been observed at TAPS experiment at MAMI (comparison of carbon and lead data) [4] with no effects on the mixed charge channel. However a detailed study of the invariant mass distributions for calcium nuclei revealed that a significant part of the effect is related to the pion Final State Interactions (FSI) [5].…”
Section: Introductionmentioning
confidence: 99%